2006
DOI: 10.1111/j.1471-6712.2006.00420.x
|View full text |Cite
|
Sign up to set email alerts
|

Doctor and patient perceptions of the level of doctor explanation and quality of patient–doctor communication

Abstract: A measure that classifies patient-doctor pairs into doctor-better and the other situations might be effective for evaluating the quality of patient-doctor communication. As this is a new approach to evaluating patient-doctor communication, more studies are necessary to verify these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 19 publications
2
19
1
3
Order By: Relevance
“…23 Studies have shown that the physician-patient communication has a significant influence on the outcome of patient care, including patient satisfaction, compliance with treatment, recall and understanding of medical information, and coping with disease. 24,25 Communication could be a key factor for choosing a Saudi as a dentist.…”
Section: Jcdpmentioning
confidence: 99%
“…23 Studies have shown that the physician-patient communication has a significant influence on the outcome of patient care, including patient satisfaction, compliance with treatment, recall and understanding of medical information, and coping with disease. 24,25 Communication could be a key factor for choosing a Saudi as a dentist.…”
Section: Jcdpmentioning
confidence: 99%
“…On a practical level, doctors' and patients' had similar views of a good consultation, identifying listening and explaining behaviours which have previously been found to be important [70,71,72,73]. Agreement on what constitutes a good interaction may be positive for patient satisfaction, understanding and adherence [74,75,76], although attitudes towards specific behaviours may differ [77], and personality differences may confound perceptions of, and preferences for, different behaviours [78,79 Interview questions intended to identify appropriate feedback content also discovered…”
Section: The Doctor-patient Relationshipmentioning
confidence: 88%
“…In the picture-based group, the surgeons were asked to use the model-design pictures to conduct communication without the model. The communication content of the groups referenced the research of Hagihara and Tarumi16 and primarily included, 1) the medical testing and examination; 2) the cause and diagnosis; 3) the treatment and its effects; 4) the side effect and treatment risks; and 5) the prognosis of the disease and patient precautions: the time for communicating was 20 min. Each season’s study continued until the research task was accomplished with 60 patients.…”
Section: Methodsmentioning
confidence: 99%